Recent sylvatic yellow fever virus transmission in Brazil: the news from an old disease - Natalia Ingrid Oliveira Silva; Lívia Sacchetto; Izabela Maurício de Rezende; Giliane de Souza Trindade; Angelle Desiree LaBeaud; Benoit de Thoisy; Betânia Paiva Drumond (Virology Journal, 2020)
Abstract Yellow fever (YF) is an acute viral disease, affecting humans and non-human primates (NHP), caused by the yellow fever virus (YFV). Despite the existence of a safe vaccine, YF continues to cause morbidity and mortality in thousands of people in Africa and South America. Since 2016, massive YF outbreaks have taken place in Brazil, reaching YF–free zones, causing thousands of deaths of humans and NHP. Here we reviewed the main epidemiological aspects, new clinical findings in humans, and issues regarding YFV infection in vectors and NHP in Brazil. The 2016–2019 YF epidemics have been considered the most significant outbreaks of the last 70 years in the country, and the number of human cases was 2.8 times higher than total cases in the previous 36 years. A new YFV lineage was associated with the recent outbreaks, with persistent circulation in Southeast Brazil until 2019. Due to the high number of infected patients, it was possible to evaluate severity and death predictors and new clinical features of YF. Haemagogus janthinomys and Haemagogus leucocelaenus were considered the primary vectors during the outbreaks, and no human case suggested the occurrence of the urban transmission cycle. YFV was detected in a variety of NHP specimens presenting viscerotropic disease, similar to that described experimentally. Further studies regarding NHP sensitivity to YFV, YF pathogenesis, and the duration of the immune response in NHP could contribute to YF surveillance, control, and future strategies for NHP conservation.